Harmony Square sebagai Wadah Interaksi Peminat Musik di Yogyakarta - , YENNI KHALIDDAZIA, Nedyomukti Imam Syafii, ST, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Music is kind of art that is the most interested by everyone. Music is also an easiest art that can be enjoyed anywhere and at any time in due to technological developments. The amount of interest in music is directly proportional to the amount of music activities, for examples music classes and music perfomances. Those many kinds of music activies take places that is able accomodate their needs. Basically people can play music in anywhere, but for convenience reason and to maximalize the audio effect, music activities must be conducted in a room that has specific acoustic system. It is also intended to prevent the environment disturbed by the music activities. Furthermore, there is a huge number in interest to learning music, but it takes high cost espacially for music course so that it becomes an obstacle for some people. Therefore, a place that is able to solve these issues is needed.